Hip abduction weakness in elite junior footballers is common but easy to correct quickly: a prospective sports team cohort based study - Osborne, H. R.; Quinlan, J. F.; Allison, G. T. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2012)
Hip abduction weakness has never been documented on a population basis as a common finding in a healthy group of athletes and would not normally be found in an elite adolescent athlete. This study aimed to show that hip abduction weakness not only occurs in this group but also is common and easy to correct with an unsupervised home based program.